Peran Pancasila sebagai Pedoman Kehidupan Berbangsa dan Bernegara dalam Dinamika Sejarah dan Perkembangannya - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Aisha Arista Widiya; Rismaya Wulandari; Riski Muhamad Sholeh Triatmojo; Ardiyan Nugraheni (Institut Nalanda, 2024)
Pancasila is the foundation and guideline of life for the Indonesian people, which contains five important values as state goals. The history of the formation of Pancasila reflects the processes and dynamics that occurred in Indonesian society, both in the pre-independence, independence and Old Order eras. In this context, Pancasila is not only considered as the basis of the state, but also as a moral and ethical guideline in the behavior of the nation. This research examines how the values of Pancasila play a role in shaping national identity and facing the challenges of globalization, as well as the importance of youth in living and implementing these values to maintain the spirit of nationhood.